(untitled) (Malaysian Journal of Learning and Instruction, 2004)
The paper is presented in two sections. In Section A, the paper explores the notion of knowledge management with reference to knowledge management of educational disciplines. In this section, the thoughts of authors and researchers who have explored various notions related to teaching and learning and societal as well as organizational change are referred in order to recognize the diversity and range of ideas directly and indirectly related to the academic disciplines which can be the subject of knowledge management in the education field. The themes referred to include teaching-leaning, thinking, technological innovations, and educational ideas. Lifestyle changes and future scenarios are also referred to. In Section B, the paper presents a preliminary attempt to discuss knowledge management at the undergraduate degree with special reference to the Bachelor of Management Program. The focus of the knowledge management pursuit is on the concentration of Quality Management. The work is work in progress. Much work needs to be done to integrate notions at the level of the terms, seminal concepts, theories and other perspectives into a coherent conceptual framework. On the one hand further integration could be conducted at the particular units of syntheses among the various subjects in the Quality Management Majors/Concentration. On the other hand, beyond the degree program, scholars could apply the lessons learned to integrate and manage their own learning in formal, non formal and informal learning areas. The encouragement to scholars/students to pursue integration of their knowledge corpus based on the assumptions of the Personal Construct Theory.